The Effort of State and Non-State Actors in Ensuring Access to Primary and Secondary Education for Indonesian Citizens in Singapore - Diah Ayu Wulandari (Institute of International Studies, 2022)
Singapore’s Ministry of Education (MOE) policy in the Singapore local schools admission that places international students as the last priority after Singapore citizens and Permanent Residents, coupled with the expensive school fees for international students are the main problems in accessing primary and secondary education faced by Indonesian citizens in Singapore. Efforts from various parties are needed to ensure the fulfillment of access to primary and secondary education for Indonesian Citizens in Singapore. This research explores state and non-state actors' efforts to ensure access to primary and secondary education for Indonesian citizens in Singapore. Data collection was obtained through interviews and a literature review. This research shows that multi-track diplomacy is established between state actors consisting of the Indonesian Embassy in Singapore and Indonesian State-Owned Enterprises as representative of track 1, and non-state actors consist of professionals (track 2), entrepreneurs (track 3), and college students (track 5). The multi-track diplomacy is reflected in the establishment of Sekolah Indonesia (Singapura) Ltd. and Pusat Kegiatan Belajar Masyarakat (PKBM) KBRI Singapura. The multi-track diplomacy is established because of shared values of humanitarianism. The collaboration of multi-track diplomacy and the spirit of humanitarianism has received positive responses from Singapore Government agencies and educational institutions, which aim to improve the quality of education at Sekolah Indonesia (Singapura) Ltd. and PKBM KBRI Singapura.